Inhibition of allergen‐dependent IgE activity by antibodies of the same specificity but different class - Dodev, T. S. (Allergy, 2015)
IgG(4) purified from patients undergoing specific allergen immunotherapy inhibits the activities of the serum IgE in in vitro assays and is thought to reduce the symptoms of the disease. However, it is not known whether this is related to an intrinsic property of this subclass or only the allergen specificity. We tested the hypothesis that allergen specificity is the critical determinant for this activity using a panel of antibodies with identical specificity but different subclasses. The different antibodies were all able to inhibit the activity of IgE to the same extent. We demonstrate that specificity is the dominant factor determining the ability of an antibody to block allergen‐dependent IgE activity.